Shoreline Change Analysis and Prediction of Sitakunda Coastline Using Satellite Imageries - Rahman, Muhammad Khalilur; Rashid, Md. Shahedur (The Jahangirnagar Review, 2024)
The term "shoreline" refers to the ever-evolving line denoting the border between water and land. This research, conducted in the Sitakunda area of Chattogram, accounted for the dynamic nature of the coast as a consequence of geomorphological and hydrological processes. The primary objective of the research is to analyze shoreline changes from 1990 to 2021. This study also tries to predict how shorelines will develop by the year 2034 using satellite imagery and the Digital Shoreline Analysis System (DSAS) in ArcMap software. Four multi-spectral satellite imageries have been used which are Landsat Thematic Map (TM) images (1990, 2000, 2011), and Landsat Operational Land Imager (OLI) images (2021) over the 31 years. The NDWI (Normalized Difference Water Index) technique was used to extract all of the previous shorelines. The shoreline change rates were calculated by using the End Point Rate (EPR) and Linear Regression Rate (LRR) method along the study area in four periods (1990-2000), (2000-2011), (2011-2021) and the global range of time (1990-2021). The highest erosion rate for the worldwide era is reported to be -16.72 m/year, while the maximum accretion rate is recorded to be 38.97 m/year. Erosion is most prominent at the shoreline’s central section, whereas accretion is most prominent along its northern and southern sections. Erosion averaged -55.33 meters per year between 2000 and 2011, whereas accretion averaged 131.02 meters per year between 2011 and 2020. Erosion predominates from 2000–2021, while accretion predominates from 1990–2000 and 2011–2021. We were able to accurately predict the shoreline’s position and length in 2034; it measured 42.78 kilometers length. The erosion and accretion area of the predicted shoreline is respectively 5.189 sq. km and 1.389 sq. km. The results identify the undisturbed and stable areas where future construction may proceed, as well as the most vulnerable areas that require immediate intervention. The DSAS approach is ideal for continuous monitoring of Sitakunda’s shifting coastline.